2015
DOI: 10.5664/jcsm.4782
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Sleep Education in Schools: A Review of Dos and Don'ts

Abstract: Study Objectives: Sleep duration and quality are associated with negative neuropsychological and psychosocial outcomes in children and adolescents. However, community awareness of this is low and sleep education programs in schools are attempting to address this issue. Several studies now exist assessing the effi cacy of these sleep education programs for improving sleep knowledge, sleep hygiene and sleep patterns. This paper presents these sleep education programs, most particularly, it presents the strengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 50 publications
4
69
2
4
Order By: Relevance
“…27 Furthermore, the study provides evidence that a cognitive behavioral and mindfulness-based group sleep intervention can improve sleep hygiene awareness among at-risk adolescents, with large effect sizes, consistent with research showing that school-based sleep intervention programs lead to improvements in students' knowledge about sleep and insomnia. [17][18][19] However, the magnitude of the effect size found in the current study was larger than those reported in RCTs of school-based sleep education programs. 70,71 This might be due to several factors.…”
Section: Hypotheses One and Two-treatment Effectscontrasting
confidence: 84%
See 2 more Smart Citations
“…27 Furthermore, the study provides evidence that a cognitive behavioral and mindfulness-based group sleep intervention can improve sleep hygiene awareness among at-risk adolescents, with large effect sizes, consistent with research showing that school-based sleep intervention programs lead to improvements in students' knowledge about sleep and insomnia. [17][18][19] However, the magnitude of the effect size found in the current study was larger than those reported in RCTs of school-based sleep education programs. 70,71 This might be due to several factors.…”
Section: Hypotheses One and Two-treatment Effectscontrasting
confidence: 84%
“…Many adolescent sleep education programs have been implemented on the premise that knowledge guides behavior. [17][18][19] However, the findings from the present study highlight that simple learning and retention do not always elicit behavior change, consistent with social cognitive models of health behavior, such as the Theory of Planned Behavior , all of which posit that factors other than knowledge and awareness can influence an individual's decision about whether or not to engage in a positive health behavior. These factors include expectations of improvement, self-efficacy, attitudes, perceived barriers, and peer and family attitudes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Sleep disturbance in adolescents can be treated using a range of approaches. Recent reviews have suggested that while school-based sleep education programs are effective for improving students' knowledge about sleep and insomnia, they are less effective for improving sleep behavior or mental health (Blunden & Rigney, 2015;Blunden, Chapman, & Rigney, 2012;Gruber, 2017). This is consistent with research showing that targeted interventions are more effective than universal interventions in preventing child and adolescent mental health problems (Rohde, 2015), and that simple sleep hygiene instruction does not guarantee positive outcomes in adults (Irish, Kline, Gunn, Buysse, & Hall, 2015).…”
Section: Introductionsupporting
confidence: 65%
“…A review of these by Blunden and Ridgney, demonstrated the importance of including others, such as parents, as sleep is affected by both cultural and environmental factors within the home. 44 Importantly, it was noted that a generic sleep programme would be unlikely to benefit all individuals. Identifying specific problems was a more useful approach and imparting knowledge alone was not enough to effect a change in behaviour.…”
Section: Assessing Sleep In Clinical Practicementioning
confidence: 99%